A Cross-Sectional Study to Assess Awareness and Practices Related to Prevention of COVID-19 amongst Shopkeepers near Medical Establishments - Shruti Shastri; Dinesh Bhatnagar (Medsci Publications, 2021)
Background: The World is experiencing Corona virus Disease 2019(COVID-19) pandemic. Respiratory and hand hygiene prevents COVID-19 infection. Shopkeepers near medical establishments have higher risk of catching and transmitting infection as they cater to patients and attendants. Awareness and practices regarding preventive measures is important for their safety. Objective: To determine awareness and practices related to prevention of COVID-19 amongst shopkeepers near medical establishments. Methods: Cross-sectional descriptive study conducted over a period of two months, started in month of March 2020 before nationwide locked down. Using simple random sampling method 160 shops near large medical establishments were selected and shopkeepers were interviewed. Results: 90 shops were of eatables, 43 medical shops and 27 others. Mean age of participants was 40.6(±14.6) years. 96.3% were males. Around 81% were found to be aware of mode of transmission, common symptoms and one or more preventive measures. Around 50% were aware of non-availability of vaccine/definitive treatment. 57.5% had hand washing facility at/near shop. Majority of people used cloth/hands while coughing/sneezing. Only 14% were wearing mask. Conclusion: Awareness of preventive measures of COVID-19 amongst shopkeepers was found to be moderate yet practices inadequate. Behavioural change communication would help inculcate respiratory and hand hygiene practices at work place.